Quantification of ergovaline using HPLC and mass spectrometry in Iranian Neotyphodium infected tall fescue - Najafabadi, A. Sobhani (Medknow Publications Pvt Ltd, 2010)
Ergovaline, the main ergopeptine alkaloid produced in tall fescue (Fescue arundinacea Schreb.) infected with endophyte (Neotyphodium coenophialum Morgan- Jones & Gams), is known to cause tall fescue toxicosis. This study was conducted to examine the presence of fungal endophytes in five populations of tall fescue collected from various regions of Iran. The existence of Neotyphodium mycelia in the tissues of the samples was confirmed by microscopic examination, and the isolation was performed from leaf tissues of the hosts on potato dextrose agar. All isolates were confirmed as the Neotyphodium species by PCR, using specific primers. Mass detection and determination of ergovaline were performed by HPLC at three plant growth stages. Ergovaline was detected in all isolates, with the mean concentrations of 0.24 to 3.48 μg/g dry matter of different populations for the whole three plant growth stages. The differences in ergovaline content between plant populations and sampling time were statistically significant. This is the first report of ergovaline content in endophyte infected Fescue arundinacea from natural grasslands in Iran.